Non-urgent encounters in a Swiss medical emergency unit (Swiss Medical Weekly, 2013)
BACKGROUND: Emergency department crowding is a growing international problem. One possible reason for crowding might be the rising number of “walk-in” patients presenting with “non-urgent” health complaints. METHODS: In a retrospective cohort study in adult medical patients presenting to the emergency unit of the University Hospital Zurich, we determined the frequency of “non-urgent” encounters, examined patient characteristics predictive for such encounters, and explored the impact of a simple, non-validated triage tool on diverting “non-urgent” cases to alternate sites of primary care. RESULTS: We included 1,175 and 1,448 medical encounters before (1–31 January 2008) and after (1–31 January 2009) the implementation of the triage tool. Almost one out of three patients presented with a minor “non-urgent” health complaint (29.9% [95%CI 28.1%–31.6%]). The most common were “cough/sneezing” (7.82% [95%CI 6.79%–8.84%]), “follow-up” (6.44% [95%CI 5.50%–7.38%]), and “weakness/tiredness” (3.47% [95%CI 2.77%–4.17%]). Significant predictors for “non-urgent” encounters were young age (mean adjusted odds ratio 0.93 [95%CI 0.88–0.97] for each additional decade of life), and non-Swiss origin (adjusted odds ratio 1.18 [95%CI 1.02–1.31]). The triage tool did not divert “non-urgent” cases from the emergency unit to outpatient care (adjusted odds ratio 0.94 [95%CI 0.80–1.12]). CONCLUSION: In the emergency unit of the University Hospital Zurich, the prevalence of “non-urgent” medical encounters was substantial with one out three patients presenting with minor health complaints. Young age and non-Swiss origin were associated with increased use of the emergency unit for “non-urgent” conditions. A simple triage tool did not effectively divert “non-urgent” cases to alternates sites of primary care.